Gastroesophageal Reflux Disease A Growing Concern - Chai, Jianyuan (IntechOpen, 2023)
Gastroesophageal reflux disease (GERD) is the most common digestive disorder in the world. It affects nearly 1.1 billion people globally, which is about 14% of the world population. GERD is having a hugely negative impact on our health and the world economy. This book provides an update on the status of GERD and the main challenges to treating this condition. We hope that it will raise more awareness of this disease among professionals and non-professionals alike.